KUNTASUKU -projekti: Suomen kuntien lapsi-, vanhus- ja väestöllisen huoltosuhteen tarkastelua maakuntatasolla käyttötalouden näkökulmasta ajanjaksolla 2015-2019 - Samuli Aho; Jari Kaivo-oja (KAKS – Kunnallisalan kehittämissäätiö, 2022)
There are worrying features in the development of Finland’s demographic popula-tion structures recently. The population is ageing, and the birth rate is falling, and the demographic structure is changing so that there are fewer people in active work-ing life than before. This development can also be seen in the developments of de-mographic, child and old-age dependency ratios as the demographic and old-age de-pendency ratio grow and the child welfare ratio decreases in the regions of Finland. Social policy has been used in various societies to even out social inequalities, to improve consumer demand and to maintain social stability. Regional policy has also pursued the same objectives. The “circle of good” produced by social policy can, at best, contribute to these societal objectives. At worst, in the so-called “circle of evil”, social problems become more acute and wicked, and cause social instability. Municipalities are important providers of welfare services, and with their operating economy income and expenditure, municipalities can potentially contribute to de-mographic development by targeting their activities correctly to achieve their goals. By 2023, the provision of municipal welfare services will be transferred to the wel-fare counties in terms of social and health care and rescue services. The welfare counties largely follow the current county boundaries. Initially, the social and health care reform in question will work on as so-called “skeletal model”. Later so-called “skeletal model” is just being transferred to a “muscle model”, i.e., a functional model for the organization of regional well-being services in the future. In connection with this above-mentioned development, the purpose of the “Kuntasuku” project has been to investigate in more detail what and what kind of statistical connections all operating economy income and expenditure per capita of all municipalities in Finland are having to different dependency ratios (i.e., the de-mographic, child, and old-age dependency ratios) at the county level. In addition, the empirical study examined in more detail how municipalities have used their income and expenditure at the regional level in various dependency relationship situations (in increasing and falling dependency ratios) of the counties. At the end of the study, the statistical links obtained were used to make rough predictions for future de-pendency ratios. The approach developed in the study can be updated and applied flexibly repeatedly as the statistical databases are updated. This new model enables data-based development of financial funding models for municipalities and wellbe-ing services counties. The study provided temporal statistical reference evidence on the effects of the al-locations of the operational economy on the dependency ratios of the children, the elderly, and the population. The local government family survey also showed how in different situations municipalities have behaved in different regions. In many Eu-ropean countries, as in Finland, there is pressure to improve the dependency ratio to a more balanced dependency ratios in the future. Decision-makers should imple-ment carefully, and data-basely tailored allocations of income and expenditure for welfare services of regions. The empirical study also partly succeeded in correctly predicting the child and old-age dependency ratios for a next year to come with the help of municipalities' operating costs and operating income at the county level. This is a promising result for further development of the regional financial planning model. This achieved result should be considered in the future planning of social and health services in the state and welfare regions. Keywords: Demographic dependency ratio, child dependency ratio, old-age de-pendency ratio, operating economy of municipalities, Finland's national economy, welfare regions Suomen väestön kehityksessä on havaittavissa viime aikoina huolestuttavia piir-teitä: väestö vanhenee ja syntyvyys laskee ja väestörakenne muuttuu sellaiseksi, että aktiivisessa työelämävaiheessa olevia henkilöitä on aikaisempaa vähemmän. Tämä kehitys on nähtävissä myös väestöllisen-, lapsi- ja vanhushuoltosuhteiden ke-hityksessä väestöllisen ja vanhushuoltosuhteen kasvaessa ja lapsihuoltosuhteen laskiessa eri maamme alueilla. Sosiaalipolitiikkaa on käytetty eri yhteiskunnissa yhteiskunnallisten eriarvoisuuk-sien tasoittajana, kulutuskysynnän parantajana ja yhteiskunnallisen vakauden ylläpitäjänä. Myös aluepolitiikkaa on harjoitettu samojen tavoitteiden edistämisessä. Sosiaalipolitiikan tuottama hyvän kehä voi parhaimmillaan edistää näitä tavoitteita, mutta pahimmillaan niin kutsutussa pahan kehässä yhteiskunnalliset ongelmat kärjistyvät ja siihen liittyvät ilmiöt aiheuttavat yhteiskunnallista epävakautta. Kunnat ovat tärkeitä hyvinvointipalveluiden tarjoajia ja käyttötalouden tuloillaan ja menoillaan ne voivat mahdollisesti vaikuttaa osaltaan väestökehitykseen kohdista-malla toimintansa oikein tavoitteidensa saavuttamiseksi. Kuntien hyvinvointipalve-luiden tarjoaminen on siirtymässä vuoteen 2023 mennessä hyvinvointialueiden hoidettavaksi sosiaali- ja terveydenhoidon ja pelastustoimen osalta. Hyvinvointialueet noudattavat pitkälti nykyisiä maakuntarajoja. Aluksi kyseinen uudistus toimii ns. luurankomallina, jossa vasta siirrytään ns. lihasmalliin eli toimivaan malliin hyvinvointipalveluiden järjestämisessä tulevaisuudessa. Tähän edellä mainittuun alueelliseen kehitykseen liittyen Kuntasuku -projektin tarkoituksena on ollut selvittää tarkemmin sitä, mitä ja millaisia tilastollisia yhteyksiä Suomen kaikkien kuntien kaikilla käyttötalouden tuloilla ja menoilla asukasta kohti on maakuntatasolla erilaisiin huoltosuhteisiin (eli väestölliseen-, lapsi- ja vanhushuoltosuhteeseen). Lisäksi tutkimuksessa selvitettiin tarkemmin, miten kunnat ovat käyttäneet maakuntatasolla tulojaan ja menojaan erilaisissa huoltosuhdetilanteissa (nousevissa ja laskevissa huoltosuhteissa). Tutkimuksen lopuksi saatujen ti-lastollisten yhteyksien avulla tehtiin karkeita ennusteita tuleville huoltosuhteille. Tutkimuksessa kehitettyä lähestymistapaa voidaan päivittää ja käyttää joustavasti yhä uudelleen tilastoaineistojen päivittyessä. Tämä uusi malli mahdollistaa tietopohjaisen kuntien ja hyvinvointialueiden rahoitusmallien kehittämistyön. Tutkimus antoi ajallisia tilastollisia viitetodisteita käyttötalouden kohdentamisten vaikutuksista lapsi-, vanhus- ja väestölliseen huoltosuhteeseen. Nyt toteutettu Kuntasuku -tutkimus osoitti myös sen, miten erilaisissa tilanteissa kunnat ovat eri maakunnissa käyttäytyneet. Parantaakseen maakuntien huoltosuhteita hyvän kehää voimistavaksi niiden tulisi käyttää jokaiselle erikseen huolellisesti ja tietopohjaisesti sovitettuja hyvinvointipalveluiden tulojen ja menojen kohdennuksia. Tutkimuksessa myös onnistuttiin maakuntatasolla osittain ennustamaan oikein vuoden päähän lapsi- ja vanhushuoltosuhdetta. kuntien käyttökustannusten ja käyttötuottojen avulla. Tämä on lupaava tulos mallin jatkokehittelyn kannalta. Tämä saavutettu tulos kannattaa huomioida valtion ja maakuntien sosiaali- terveyspalveluiden tulevan suunnittelun osalta.
Asiasanat: väestöllinen huoltosuhde, lapsihuoltosuhde, vanhushuoltosuhde, kuntien käyttötalous, Suomen kansantalous, hyvinvointialueet